(untitled) (Scientific journal of the Fergana State University, 2024)
Man was created for culture, art and literature to live next to him, forming and developing as part of his spiritual image. This article is intended to highlight culture, art, types of art, artistic creativity, artistic perception, as well as the role and significance of spiritual education in the field of culture and art. An analytical method was used. As a result, the nature of culture and art is revealed. The study of these issues is important in stabilizing the socio-spiritual environment of society.